(untitled) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2022)
Several models can be used to mimic the temperature-dependent growth rate of microorganisms on different media. Arrhenius is a popular model because of its small number of parameters. Microbial growth and metabolic activity on their substrates are generally affected by temperature. Microbes are vulnerable to temperature changes because of their small size. With a chevron-like discontinuous graph of apparent activation energy and a breakpoint, growth on diesel by Alcaligenes sp. YLA11 is described showing a breakpoint at 28.05 °C. Regression analysis resulted in two activation energies: 20–27 °C and 30–42 °C with the activation energies of 41.72 kJ/mol and 84.72 kJ/mol, respectively. For the examined temperature range (30-42 °C), a Q10 value of 2.905 and a theta value of 1.11 was calculated. Predicting the breakdown of diesel and its movement during bioremediation is an output that can be predicted by parts of this study.